Risk factors for overuse shoulder injuries in a mixed-sex cohort of 329 elite handball players: previous findings could not be confirmed - Andersson, S. H.; Bahr, R.; Clarsen, B.; Myklebust, G. (British Journal of Sports Medicine, 2018)
Background: Shoulder injuries are common among handball players and predominantly characterised by overuse characteristics. Reduced total glenohumeral rotation, external rotation weakness and scapular dyskinesis have been identified as risk factors among elite male handball players.